Start a fire, kill the bug: The role of platelets in inflammation and infection. Issue 6 (August 2018) - Deppermann, Carsten; Kubes, Paul
Platelets are the main players in thrombosis and hemostasis; however they also play important roles during inflammation and infection. Through their surface receptors, platelets can directly interact with pathogens and immune cells. Platelets form complexes with neutrophils to modulate their capacities to produce reactive oxygen species or form neutrophil extracellular traps. Furthermore, they release microbicidal factors and cytokines that kill pathogens and influence the immune response, respectively. Platelets also maintain the vascular integrity during inflammation by a mechanism that is different from classical platelet activation. In this review we summarize the current knowledge about how platelets interact with the innate immune system during inflammation and infection and highlight recent advances in the field.